The telomere/telomerase binding factor PinX1 is a new target to improve the radiotherapy effect of oesophageal squamous cell carcinomas. Issue 5 (22nd February 2013) - Qian, Dong; Zhang, Bin; He, Li‐Ru; Cai, Mu‐Yan; Mai, Shi‐Juan; Liao, Yi‐Ji; Liu, Yan‐Hui; Lin, Marie C; Bian, Xiu‐Wu; Zeng, Yi‐Xin; Huang, Jun‐Jian; Kung, Hsiang‐Fu; et al.
Abstract Chemoradiotherapy (CRT) is a standard treatment for oesophageal squamous cell carcinoma (ESCC) in its advanced stages. The telomerase/telomere interacting protein PinX1 contributes to telomere maintenance, tumourigenicity, and influences the DNA damage agent‐induced apoptotic response in telomerase‐positive cancer cells. However, the clinical and biological significance of PinX1 in human ESCCs remains unclear. We examined the expression dynamics of PinX1 by immunohistochemistry in a learning cohort (n = 98) and a validation cohort (n = 59) of ESCC patients treated with definite chemoradiotherapy (CRT). A series of in vivo and in vitro assays were performed to elucidate the effect of PinX1 on ESCC cells' CRT response and underlying mechanisms. Knockdown of PinX1 did not affect ESCC cells' chemosensitivities to 5‐fluorouracil and cisplatin, but substantially increased ESCC cells' therapeutic efficacy of radiation both in vitro and in vivo. Ectopic overexpression of PinX1 dramatically enhanced ESCC cells' resistance to radiotherapy. Furthermore, we demonstrated that PinX1 resistance to radiotherapy (RT) was attributed to PinX1 maintaining telomere stability, reducing ESCC cell death by RT‐induced mitosis catastrophe (MC). High expression of Pinx1 correlated positively with ESCC's resistance to CRT, and was a strong and independent predictor for short disease‐specific survival (DSS) of ESCC patients. Our data suggest that PinX1 could serve as a novel predictor for a CRT response to ESCC patients, and the pathway of PinX1‐mediated telomere stability might represent a new target to improve the RT effect of ESCC. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.